Post-error behavioral adjustments under reactive control among older adults - Tsuchida, Noriaki; Kasuga, Ayaka; Kawakami, Miki (Frontiers in Psychology, 2022)
This study analyzed the effects of aging on post-error behavioral adjustments from the perspective of cognitive control. A modified error awareness task was administered to young (n = 50) and older (n = 50) adults. In this task, two buttons were placed on the left and right sides in front of the participants, who were instructed to use the right button to perform a go/no-go task, and were notified if they made an error. There were three experimental conditions (A, B, and C): participants had to push the right button once in Condition A and twice in Condition B and C when a go-stimulus was presented. Conversely, participants were asked to withhold their response when a no-go stimulus was presented. Response inhibition differed depending on the experimental condition. The participants were asked to push the left button as quickly as possible when an error occurred. The results showed relatively longer reaction times to sudden errors among older adults compared with young adults. Furthermore, the difference in the error responses (i.e., accidentally pushing the right button once or twice when a no-go stimulus was presented) strongly influenced older adults’ response time after an error. These results suggest that the shift from proactive to reactive control may significantly influence post-error behavioral adjustments in older adults.